AXILLARY SURGERY IN BREAST CANCER: ACUTE POSTOPERATIVE COMPLICATIONS IN A HOSPITAL COHORT OF WOMEN OF RIO DE JANEIRO, BRAZIL - Macedo, Flávia Oliveira; Bergmann, Anke; Koifman, Rosalina Jorge; Torres, Daniele Medeiros; Costa, Rejane Medeiros; Silva, Ilce Ferreira da (Mastology, 2018)
Objective: To analyze the incidence of early postoperative complications in women with breast cancer according to the axillary surgery. Methods: An observational study of a cohort of women diagnosed with T1-T2N0M0 clinical stage breast cancer attended at the Brazilian National Cancer Institute from January 2007 to December 2009. The outcome was defined as postsurgical complications in the affected upper limb, such as: axillary web syndrome, winged scapula, paraesthesia and surgical wound, seroma and wound infection. The incidence of simple complications was estimated. The crude and adjusted Odds Ratios, with their respective 95% confidence intervals, were estimated by Multiple Logistic Regression analysis. Results: The incidence of postoperative complications was significantly lower in sentinel lymph node biopsy (axillary web syndrome: 6.0%; paraesthesia: 45.2%; winged scapula: 9.1%; seroma: 28.5%; wound infection: 3.8%) than in axillary lymphadenectomy (axillary web syndrome: 22.5%; paraesthesia: 89.8%; winged scapula: 50.0%; seroma: 69.4%; wound infection: 12.9%). Compared to those who underwent axillary lymphadenectomy, the risk of postoperative complications in those in whom sentinel lymph node biopsy was performed was significantly lower. Conclusion: The sentinel lymph node biopsy technique was an independent protective factor for acute postoperative complications when compared to axillary lymphadenectomy.